Gender mainstreaming in development planning : a reference manual for governments and other stakeholders - Taylor, Viviene (Commonwealth Secretariat LondonUS, 1999)
Provides guidance for governments and other organizations who seek to mainstream gender in development planning. Looks at approaches to development planning (DP) and highlights the need to address the practical and the strategic gender needs of women. Examines major DP issues including: political will and adequate financial and other resources; macroeconomic policy; the need for a co-ordinated approach; and for participant involvement. Looks at efforts by the Indian and South African governments to advance gender equality.